2021
DOI: 10.1177/15500594211026280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of Electroencephalography in the Assessment of Acute Thermal Pain: A Narrative Review Based on Articles From 2009 to 2019

Abstract: Nowadays, no practical system has successfully been able to decode and predict pain in clinical settings. The inability of some patients to verbally express their pain creates the need for a tool that could objectively assess pain in these individuals. Neuroimaging techniques combined with machine learning are seen as possible candidates for the identification of pain biomarkers. This review aimed to address the potential use of electroencephalographic features as predictors of acute experimental pain. Twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Our heterogeneous sample is representative of the diverse presentations of chronic pain patients seeking clinical care and increases the generalizability of our model to various pain phenotypes. Prior literature focused predominantly on spectral EEG features, a limitation that has been noted previously ( 32 ). Our methods included spectral, entropy, functional connectivity, and graph theory feature types, many of which were previously unexplored in pediatric chronic pain participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our heterogeneous sample is representative of the diverse presentations of chronic pain patients seeking clinical care and increases the generalizability of our model to various pain phenotypes. Prior literature focused predominantly on spectral EEG features, a limitation that has been noted previously ( 32 ). Our methods included spectral, entropy, functional connectivity, and graph theory feature types, many of which were previously unexplored in pediatric chronic pain participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several EEG features, including spectral power derived from both fast Fourier ( 27 , 28 ) and continuous wavelet ( 29 ) transformations, functional connectivity ( 27 ), and time-frequency outcomes ( 30 , 31 ), differentiate between resting (e.g. no pain) and tonic cold pain conditions in heathy participants, with frontal theta rhythms appearing particularly sensitive to cold pain ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pediatric neuroimaging literature has concentrated on employing fMRI in adolescents with complex regional pain syndromes (CRPS), 24 , 41 , 66 , 71 identifying that pediatric and adult CRPS patients show different patterns of functional connectivity changes. 80 This finding supports studies identifying age-dependent developmental changes in pediatric pain processing, perception, and responses.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 7 , 17 , 30 There is substantial impetus for extending the findings of the adult chronic pain EEG literature to pediatric populations. This study used EEG to interrogate brain activity and connectivity changes, previously observed in adult studies, 66 , 74 in youth with chronic MSK pain at rest and during thermal experimental pain modalities (tonic heat and cold pressor task). We hypothesized that youth with chronic MSK pain will show developmental patterns of EEG neural activity and connectivity differences to age-matched pain-free controls at rest and an increased sensitivity to acute tonic pain experiences during thermal experimental pain modalities.…”
Section: Introductionmentioning
confidence: 99%